Effect of biochar and phosphorus fertilizer application on selected soil properties and agronomic performance of chickpea (Cicer arietium) - Lusibisa, Siphiwe Gloria (My University, 2015)
See the attached abstract below
MSCAGR ( Soil Science)
Department of Soil Science
Keywords: Biochar; Soil degradation; UCTD; Organic carbon; Soil properties; Crop yield; water use efficiency; 631.850968257; Phosphorus in agriculture -- South Africa -- Limpopo; Agriculture -- South Africa -- Limpopo; Phosphates -- South Africa -- Limpopo; Phosphates fertilizers -- South Africa -- Limpopo; Chickpea -- South Africa -- Limpopo; Crop yield -- South Africa -- Limpopo